2018
DOI: 10.1093/jas/sky064
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for fecal egg counts and their relationship with body weights in Katahdin lambs

Abstract: Reliance on anthelmintic drugs to control internal parasites in sheep is no longer sustainable because of the development of resistance to these drugs in parasite populations. Genetic selection may offer an alternative long-term solution, as differences in parasite resistance exist both within and among sheep breeds. However, selection for parasite resistance may have correlated effects on other production traits. The objectives of this study were to estimate genetic parameters for weaning (WFEC) and postweani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Heritability estimates for FEC in peri-parturient ewes were 0.35 ± 0.06 at lambing and 0.24 ± 0.07 at 30 d postpartum and somewhat higher than heritability estimates for FEC of 0.19 to 0.24 in growing Katahdin lambs (Ngere et al, 2018). These results suggest that genetic improvement in parasite resistance in Katahdin sheep is possible for both growing lambs and peri-parturient ewes.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Heritability estimates for FEC in peri-parturient ewes were 0.35 ± 0.06 at lambing and 0.24 ± 0.07 at 30 d postpartum and somewhat higher than heritability estimates for FEC of 0.19 to 0.24 in growing Katahdin lambs (Ngere et al, 2018). These results suggest that genetic improvement in parasite resistance in Katahdin sheep is possible for both growing lambs and peri-parturient ewes.…”
Section: Discussionmentioning
confidence: 74%
“…Bivariate models for lamb FEC and ewe NLB and NLW included only direct additive covariances between the pairs of traits. Univariate models for lamb FEC (Ngere et al, 2018) revealed no significant maternal additive or dam permanent environmental effects on lamb FEC, and these effects therefore did not appear in bivariate models involving lamb FEC. Covariances between residual effects on lamb FEC and future permanent environmental and residual effects on ewe NLB and NLW were also assumed equal to 0.…”
Section: Correlations Among Traitsmentioning
confidence: 93%
See 2 more Smart Citations
“…Some mature Katahdin ewes have been shown to have GIN resistance traits similar to St Croix upon natural infection (Burke & Miller ). Recent work estimated the heritability ( h 2 ) of FEC in Katahdin lambs at 60 ( h 2 = 0.18–0.26) and 120 ( h 2 = 0.23–0.46) days of age (Ngere et al ), and periparturient ewes at lambing ( h 2 = 0.29–0.41) and 30 days postpartum ( h 2 = 0.17–0.31) (Notter et al ). These generally moderate heritabilities for FEC suggest that parasite resistance can be improved through genetic selection.…”
mentioning
confidence: 99%